Principles of plant genetics and breeding - Acquaah, George (Hoboken: Wiley Blackwell, 2021)
"Principles of Plant Genetics and Breeding, 3rd Edition introduces both classical and molecular tools for plant breeding. Topics such as biotechnology in plant breeding, intellectual property, risks, emerging concepts (decentralized breeding, organic breeding), and more are addressed in the updated edition of this text. Industry highlight boxes are included throughout the text to contextualize the information given through the professional experiences of plant breeders. The final chapters provide a useful reference on breeding the largest and most common crops. New to this edition - A more comprehensive list of molecular markers: Allozyme, RFLPs, RAPD, SSR, ISSR, DAMD, SCoT, AFLP, SNPs, ESTs, SCAR, DArT, RAMP. A table of comparison of these markers will be included. New plant breeding techniques will be discussed, including - (NPBTs): Zinc finger nuclease, TALE nuclease (TALENs), Oligonucleotide directed mutagenesis (ODM), Cisgenesis and intragenesis, RNA-dependent DNA methylation (RdDM), Grafting on GM stock, Reverse breeding, Agro-infiltration, Genome editing (CRSPR-Cas system). Section on breeding selected crops will be removed (based on feedback from readers/reviewers). Industry highlights within the main text will highlight applications of some breeding methods in other chapters"--
Includes index.
Also issued in electronic format.
Keywords: Plant breeding; Plant genetics